The role of micro-CT in breast cancer management: a systematic review on the clinical applications of micro-CT in breast cancer and a diagnostic accuracy meta-analysis on intraoperative margin assessment - Meshkati Yazd, Seyed Mostafa; Vasigh, Mahtab; Papazoglou, Andreas S.; Liatsos, Alexandros C.; Ranjbar, Keivan; Williams, Austin D.; Bleicher, Richard J.; Katsamenis, Orestis L.; Pierotti, Mathew L.; Cruz Pico, Christian X.; Theocharis, Stamatios; Tsolaki, Fani; et al. (Frontiers in Medical Engineering, 2025)
BackgroundThere is a growing interest in exploring intraoperative methods for margin assessment of malignant breast specimens in breast-conserving surgeries (BCS). Micro-computed tomography (micro-CT) has already exhibited clinical value, yielding high-resolution three-dimensional (3D) volumetric images. Against this background, this study aimed to systematically evaluate the role of micro-CT in intraoperative margin assessment (IMA) in BCS.MethodsA systematic literature review has been conducted in Scopus, EMBASE, and PubMed up to 10 December 2024. Studies reporting the diagnostic indices of micro-CT for IMA compared to histopathologic results were utilized for a diagnostic accuracy meta-analysis.ResultsEight out of the initially retrieved 2,921 studies evaluated the role of micro-CT in IMA and were eligible for calculating the pooled diagnostic indices. In those studies, 988 specimens/margins were scanned, and the scanning time ranged from 4 to 30 min. The pooled diagnostic indices were: a sensitivity of 0.63 (95% CI: 0.45–0.79), a specificity of 0.78 (95% CI: 0.68–0.85), and an accuracy of 0.77 (95% CI: 0.71–0.84) for micro-CT based IMA compared to the gold-standard histopathological assessment.ConclusionThis study demonstrates that micro-CT imaging is a promising IMA technique for BCS by providing high-resolution 3D images. These images can be acquired within a few minutes, allowing surgeons to assess margin status intra-operatively, and identify more than 70% of positive margins where reoperation rates are likely to decrease. Although these findings are encouraging, their clinical translation is still under investigation, and adequately empowered clinical trials are warranted to investigate the re-excision and local recurrence rates after micro-CT IMA assessment.Systematic Review Registrationhttps://osf.io/342h8.